Pembelajaran Bahasa dan Sastra Indonesia yang Berkarakter - Supardi Supardi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Language is a system that has function for communication tool. To do this prime function, language uses the esthetics to cover its morality messages, values or meaning. In language and literary learning compulsory the students to read and analyze the novels. The power of literary has been in language expression, language role as the builder the nation characters actually had been started. It can see in Siti Nurbaya (Marah Roesli) style, Layar Terkembang (Sutan Takdir Alisjahbana), Harimau!Harimau! (Mochtar Lubis), Burung-Burung Manyar (Y.B. Mangunwijaya), Ronggeng Dukuh Paruh (Ahmad Tohari), Para Priyayi (Umar Kayam), and Saksi Mata (Seno Gumira Ajidarma). Language expressions and esthetics in literary works has etics values that can build nation characters and new characters that it be up to date.